2002
DOI: 10.1034/j.1600-0560.2002.290510.x
|View full text |Cite
|
Sign up to set email alerts
|

Acral pseudolymphomatous angiokeratoma of children: immunohistochemical and clonal analyses of the infiltrating cells

Abstract: Our data support the idea that this disorder represents a reactive process. The modified term 'papular angiolymphoid hyperplasia' would define this disorder more appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 12 publications
4
53
0
2
Order By: Relevance
“…The possibility of APACHE was excluded by immunohistochemical studies which showed a predominance of CD3 over CD20 cells, unlike equal numbers of CD3 and CD20 as seen in APACHE. [4] Another distinguishing feature is the presence of thick walled blood vessels in APACHE in contrast to the vessels lined by plump endothelial cells in TRAPP as was seen in our cases. Apart from these features, TRAPP presents as a solitary papule and in APACHE multiple papules are noted.…”
Section: Discussionmentioning
confidence: 58%
“…The possibility of APACHE was excluded by immunohistochemical studies which showed a predominance of CD3 over CD20 cells, unlike equal numbers of CD3 and CD20 as seen in APACHE. [4] Another distinguishing feature is the presence of thick walled blood vessels in APACHE in contrast to the vessels lined by plump endothelial cells in TRAPP as was seen in our cases. Apart from these features, TRAPP presents as a solitary papule and in APACHE multiple papules are noted.…”
Section: Discussionmentioning
confidence: 58%
“…Initially, Ramsay et al thought that vascular tumors (angiokeratomas) and an associated nevoid disorder might be the origin of the disease [1]. Currently, the majority of the authors supports an inflammatory origin and believes APACHE to be a variant of pseudolymphoma [3][4][5]. Its exact cause is still unknown.…”
Section: Clinical Lettermentioning
confidence: 93%
“…Another advantage of this name is that it does not refer to a special localization or age group. Small papular pseudolymphoma [8] Small lymphoid papules of the extremities [8] Papular angiolymphoid proliferation with epithelioid features in adults and children [9] Angiolymphoid hyperplasia with high endothelial venules [10] Acral angiokeratoma-like pseudolymphoma [11] Papular angiolymphoid hyperplasia [4] Angiolymphoid hyperplasia [5] Pseudolymphomatous angiokeratoma [3] …”
Section: Clinical Lettermentioning
confidence: 99%
“…Immunhistochemisch besteht ein Gemisch von B-und T-Zellen, bei einer CD4:CD8-Ratio von  [4,5]. Die Plasmazellen produzieren zu gleichen Teilen Kappa-und Lambda-lmmunglobulinleichtketten [3,8]. Mittels Rearrangementuntersuchungen konnte ein polyklonales Infiltrat sowohl für Tals auch für B-Zellen nachgewiesen werden [3,6].…”
Section: Laborunclassified
“…Das Infiltrat ist "top heavy", gemischtzellig, polyklonal, kann Lymphfollikel ausbilden, und die Gefäße weisen Charakteristika von sog. "high-endothelial venules" der parakortikalen Areale der Lymphknoten auf [3,5,6]. Als ursächli-cher Faktor wird von einigen Autoren eine posttraumatische Genese angenommen, was durch das gehäufte Auftreten an den Akren und auch entsprechenden anamnestischen Angaben belegt wird [2].…”
Section: Zusammenfassung · Abstractunclassified